(untitled) (The Pakistan Development Review, 1999)
After remaining low throughout the 1970s and 1980s, Bangladesh’s trade deficits (as percent of GDP) with India have been rising sharply since 1993. The size of its illegal trade deficits with India is also large and perceived to be rising since the early 1990s. Thus, instead of interdependence between two trading neighbours at the same stage of development, the Bangladesh-India trade relations suggest an absolute dependence of Bangladesh on India. The debate that has now generated in Bangladesh from such a onesided trade flow has two polar themes. At one extreme are those commentators who consider Bangladesh’s large and growing trade deficits with India as a "natural and positive development" on the grounds that India is believed to be at a higher stage of development and to have gained technological maturity in the production of those goods that Bangladesh imports from India. The alternative view is that Bangladesh’s large and growing trade deficits are a recent phenomenon and have nothing to do with India’s technological maturity or prowess. As an explanation, such deficits are c9nsidered to be the result both of India’s deep devaluation policy and tariff and non-t ff barriers to Bangladesh’s exports to its markets. This paper examines the disaggregated structure of trade, as well as the revealed comparative advantage of Bangladesh and India and finds no support for the thesis of Bangladesh’s technological imports from India on grounds of their maturity. It then examines the sensitivity of trade flows between the two countries to exchange rates and the possible role of trade liberalisation in generating trade deficits within the framework of intra-industry trade models for differentiated products. The available evidence suggests that through subsidies, interventions and deep devaluation policy, India has artificially created a comparative advantage over Bangladesh in differentiaied products. India has also managed to keep its markets closed for Bangladesh’s products despite trade negotiations, between the governments. This gives credence to the suggestion that Bangladesh’s trade with India is neither fair nor competitive. Finally, the paper considers the political economy of the large and growing trade imbalances between them before drawing policy conclusions.